Updated Management of Osteoarthritis: A Review - Islam, Md. Jahidul; Yusuf, Md Abdullah; Hossain, Md Shahadat; Ahmed, Monzur (Journal of Science Foundation, 2015)
The goals of the treatment of osteoarthritis (OA) are to alleviate pain and minimize loss of physical function. To the extent that pain and loss of function are consequences of inflammation, of weakness across the joint, and of laxity and instability, the treatment of OA involves addressing each of these impairments. Comprehensive therapy consists of a multimodality approach including non-pharmacologic and pharmacologic elements. Patients with mild and intermittent symptoms may need only reassurance or non-pharmacologic treatments. Patients with ongoing, disabling pain are likely to need both non-pharmaco- and pharmacotherapy. Treatments for knee OA have been more completely evaluated than those for hip and hand OA or for disease in other joints. Thus, while the principles of treatment are identical for OA in all joints, we shall focus below on the treatment of knee OA, noting specific recommendations for disease in other joints, especially when they differ from those for disease in the knee. DOI: http://dx.doi.org/10.3329/jsf.v11i2.21597 Journal of Science Foundation, 2013;11(2):49-55